2002
DOI: 10.1093/ajcn/76.6.1367
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the antioxidant effects of Concord grape juice flavonoids α-tocopherol on markers of oxidative stress in healthy adults

Abstract: In healthy adults, 10 mL CGJ. kg(-1). d(-1) increased serum antioxidant capacity and protected LDL against oxidation to an extent similar to that obtained with 400 IU alpha-tocopherol/d but decreased native plasma protein oxidation significantly more than did alpha-tocopherol. CGJ flavonoids are potent antioxidants that may protect against oxidative stress and reduce the risk of free radical damage and chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
150
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(160 citation statements)
references
References 55 publications
3
150
0
3
Order By: Relevance
“…In our study, the amount of C in the seed extracts was 120-fold higher than the sum in the extract of the skin and grape juice. The data for the C of the seed was in agreement with previous studies (7,9,25). The antioxidant activity of the grape seed extracts comes mainly from their flavonoid contents, mostly anthocyanins and flavanols.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the amount of C in the seed extracts was 120-fold higher than the sum in the extract of the skin and grape juice. The data for the C of the seed was in agreement with previous studies (7,9,25). The antioxidant activity of the grape seed extracts comes mainly from their flavonoid contents, mostly anthocyanins and flavanols.…”
Section: Discussionsupporting
confidence: 92%
“…In the case of human subjects, although some studies reported no effect on plasma antioxidant capacity after supplementation with grape-derived products (98) , most of the trials did find some effect; for instance, increased plasma antioxidant capacity was observed after the intake of polyphenol extracts from red wine (32) , from grapes (33) , grape juice (65) , concentrated grape juice (80) , grape pomace (99) and red wine (77) . Also, studies on the possible effect of grape polyphenols in the postprandial phase have reported that after a meal accompanied by red wine, plasma antioxidant capacity by the total radical-trapping antioxidant parameter assay was sustained in type 2 diabetic subjects, whereas after the same meal without wine there was a significant decrease in antioxidant capacity (100) .…”
Section: Plasma Antioxidant Capacitymentioning
confidence: 99%
“…Nevertheless, Waddington et al (84) found no change in plasma isoprostanes or in hydroxyeicosatrenoic acids after red wine supplementation to apoE-deficient mice. Similarly, there was no change in this biomarker after the intake of concentrated grape juice (80) or grape seed polyphenols (46) by human subjects. Once again, these differences may be due to the different doses employed or to the phenolic composition of the tested products.…”
Section: Oxidation Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…O suco de uva, bebida não-alcoólica, apresenta efeitos como manutenção da função endotelial, diminuição da agregação plaquetária, aumento da capacidade antioxidante e proteção contra oxidação do LDL (O'BYRNE et al, 2002;STEIN et al, 1999). Em 2004, a American Dietetic Association, em seu documento sobre alimentos funcionais, considerou o vinho tinto e o suco de uva como bebidas com evidências "moderadas a fortes" na prevenção da agregação plaquetária em ensaios in vitro, in vivo e em estudos epidemiológicos.…”
unclassified